Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamanetworkopen.2020.21182
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Process and Outcomes of Care for Patients With Acute Myocardial Infarction in China From 2001 to 2015

Abstract: Key Points Question What are the variations in process of care and outcomes for patients with acute myocardial infarction in China by geographic area? Findings In this cross-sectional study of 27 046 hospitalizations from 2001 to 2015, patients in the region with worst performance were 17% less likely to receive optimal treatments comparing with the region with the best performance. Patients experienced a higher risk of in-hospital death by 46% in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 22 publications
3
29
3
Order By: Relevance
“…The western region, which had the best performance in processes of care, such as use of clopidogrel, ACE inhibitors/angiotensin receptor blockers and statins, had worse mortality than hospitals in the central region, which had worse performance on processes of care. 24 However, second, we did find a decrease in the proportion of patients eligible for reperfusion on admission, with one of the drivers being increased prehospital delay, which may have masked the potential benefit of increased reperfusion rate among those eligible as observed at a cohort level. Further, we found that although marked shifts in acute reperfusion therapy occurred with a move from fibrinolysis to pPCI, among reperfused patients the time to reperfusion increased in 2015.…”
Section: Discussionmentioning
confidence: 63%
“…The western region, which had the best performance in processes of care, such as use of clopidogrel, ACE inhibitors/angiotensin receptor blockers and statins, had worse mortality than hospitals in the central region, which had worse performance on processes of care. 24 However, second, we did find a decrease in the proportion of patients eligible for reperfusion on admission, with one of the drivers being increased prehospital delay, which may have masked the potential benefit of increased reperfusion rate among those eligible as observed at a cohort level. Further, we found that although marked shifts in acute reperfusion therapy occurred with a move from fibrinolysis to pPCI, among reperfused patients the time to reperfusion increased in 2015.…”
Section: Discussionmentioning
confidence: 63%
“…Our results provide a guide in terms of critical targets for improving the quality of care for PCI. 12 Furthermore, Japan is one of the fastest ageing countries, and the number of Japanese adults aged ≥65 years constitutes nearly a quarter of the total population. 33 The unique healthcare policies in Japan have led to outstanding population health and equity at low cost 34 ; however, the burden of the ageing society has placed pressures on the appropriate use of healthcare resources and expenditures in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that measuring the quality of care to identify regional variations has been central for improving the outcomes of patients undergoing PCI. 10 , 11 , 12 , 13 , 14 The research on regional variations in the management of coronary artery disease have focused on patients with acute coronary syndrome (ACS). 15 , 16 , 17 Few studies have evaluated variations in the management of elective cases, comprising most PCIs that are currently performed, and are more amenable to implementation efforts promoting standardised recommendations from clinical practice guidelines.…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 Morever, significant geographical variations and hospital-level differences persist in process of care and outcomes for patients with STEMI in China. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…A national study showed that central China had the lowest reperfusion rate among the three areas of China (western, central, or eastern), but the best mortality outcomes. 10 In rural areas of China, secondary hospitals are often first-visited hospitals for patients of STEMI. However, the proportion of secondary hospitals included in national prospective multicentre STEMI clinical trials was very low, approximately 26% in the China Acute Myocardial Infarction Registry, 12 and 22% in the ongoing Improving Care for Cardiovascular Disease in China—Acute Coronary Syndrome project.…”
Section: Introductionmentioning
confidence: 99%